Effects of infant weight gain on subsequent allergic outcomes in the first 3 years of life - Evelyn Xiu-Ling Loo; Anne Goh; Izzuddin Bin Mohd Aris; Oon Hoe Teoh; Lynette Pei-Chi Shek; Bee Wah Lee; Yiong Huak Chan; Mya Thway Tint; Shu-E Soh; Seang-Mei Saw; Peter Gluckman; Keith M Godfrey; et al. (BMC, 2017)
Abstract Background The association between early weight gain and later allergic outcomes has not been well studied. We examined the relation between weight gain and the subsequent development of allergic outcomes in the first 36 months of life in a Singapore birth cohort. Methods In repeated visits in the first 15 months, we measured infant weight and administered questionnaires ascertaining allergic outcomes. At ages 18 and 36 months, we administered skin prick tests (SPTs) to inhalant and food allergens. Results At 18 months, 13.5% had a positive SPT, 3.5% had wheeze and a positive SPT, 3.9% had rhinitis and a positive SPT, and 6.1% had eczema and a positive SPT. Higher weight gain from 6 to 9 months, 9 to 12 months and 12 to 15 months were independently associated with a reduced risk of developing a positive SPT at 18 months (p-trend ≤0.03). At 36 months, 23.5% had a positive SPT, 11.9% had wheeze and a positive SPT, 12.2% rhinitis and a positive SPT, and 11.5% eczema and a positive SPT. Higher weight gain from 12 to 15 months was associated with a reduced risk of developing a positive SPT at 36 months (p-trend <0.01). No significant associations were observed between weight gain in any period and wheeze, rhinitis or eczema combined with a positive SPT at 18 or 36 months. Conclusion Higher weight gain in the first 15 months of life was associated with a reduced risk of allergen sensitization, but not with combinations of allergic symptoms. Trial registration NCT01174875 Registered 1 July 2010, retrospectively registered.